The Interleukin-6 (rs1800797) Variant in Healthy Individuals at Medan City, North Sumatera Province - Mutiara Indah Sari1*, Siti Syarifah2 , Milahayati Daulay3 , Zaimah Z Tala4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
The Interleukin-6/IL6 (rs1800797) variant play a role in several diseases pathogenesis. The frequencygenotype of IL6 (rs1800797) varied based on different race, ethnicity, and underlying character inpopulation. This study aimed to assess the frequency of genotype and allele of IL6 (rs1800797) in healthyindividuals at Medan city, North Sumatera Province Province and this study can be used as a reference indetermining of several diseases for further studies. Genotyping of IL6 (rs1800797) in the promoter regionusing polymerase chain reaction and restriction fragment length polymorphism method, analysis using FokIrestriction enzyme. This study showed that the genotype frequency of GG, GA, and AA were 95.8 %, 4.2%, and 0 %, respectively. The allele frequency of G and A were 97.9 % and 2.1 %, respectively. The resultsindicated that the homozygous wild-type (GG) of IL6 (rs1800797) was higher than the heterozygous mutant(GA) and there was absent of homozygous mutant (AA) in this population. The frequency of G allele alsohigher than A mutant allele.